Self-Care Practice among Patients with Chronic Obstructive Pulmonary Diseases - Sharma, Kalpana; Subba, Hem Kumari; Poudyal, Sunita; Adhikari, Shital (Journal of Nepal Health Research Council, 2024)
Background: Self-management behaviour is crucial for halting the progression of the disease and preventing exacerbations and hospitalizations in patients with chronic obstructive pulmonary diseases. Hence, this study aimed to assess self-care practice among patients with chronic obstructive pulmonary diseases attending at a teaching hospital.Methods: Cross-sectional study was carried out among 106 patients who were diagnosed to have Chronic Obstructive Pulmonary Diseases and attending at respiratory and critical care medicine department of Chitwan Medical College Teaching Hospital. Convenience sampling technique was used to select 106 samples for the study. Structured interview schedule and observation checklist were used to collect the data. Data analysis was performed in SPSS version 23 for window using descriptive and inferential statistics.Results: The finding of this study revealed that 50.0% of patients with Chronic Obstructive Pulmonary Diseases had high and 50.0% had low self-care practice. Only 5.7% were using inhaler correctly whereas 94.3% of patients were using inhaler incorrectly, Furthermore, marital status, ethnicity and level of depression were found to be the significant factors associated with self-care practice of the patients.Conclusions: Half of the patients with chronic obstructive pulmonary diseases have low self-care practice whereas almost all are using inhaler incorrectly. Hence, self-management intervention program is needed for the patients with chronic obstructive pulmonary diseases to enhance their knowledge and skill on self-care practice including inhaler use.Keywords: Chronic obstructive pulmonary diseases; patients; self-care practice.